The queens and royal women of Sweden, C. 970-1330 - Wilhelmsson, Caroline, author.
1 online resource
Keywords: This is the first major piece of scholarship to provide an overview of the lives of Sweden's earliest documented queens, together with some of their most influential female relatives, who lived between 970 and 1330. Spanning a period over 350 years, approximately 40 biographies are included from the semi-legendary Viking queen Sigrid Storrda to Duchess Ingeborg of Norway, the first female de jure and de facto ruler of Sweden. Rather than merely summarising previous research, this study offers new perspectives on the evolution of queenship in medieval Sweden. It tracks the different religious, political, and socio-economic trends which defined and shaped the office of queen and identifies three main phases of development which led to royal women's economic and political emancipation by the mid-fourteenth century. The study's main strength lies in its close reading and novel interpretation of the surviving primary sources, enabling readers to understand the importance of these women and wider themes such as state formation, Christianisation, and international politics. The Queens and Royal Women of Sweden, c. 970-1330 is of interest to scholars of queenship and gender studies, medieval historians in general, those with an interest in ecclesiastical history, and anyone studying medieval Scandinavia.